Effect of Corrosion on Steel Strength (ST. 37) - Sundari, Titin; Mutrofin, Akmam; Ramadhani, Rahma; Khiyana, A'izzatul; Yulianto, Totok; Nugroho, Meriana Wahyu (ASTONJADRO, 2024)
Rust on steel is often a problem in construction work. Rust occurs when iron oxidizes. The cause is prolonged exposure to water, air, or an acidic environment. Iron will bind oxygen atoms in the air to form iron oxide/rust. Rust continues to increase, accelerating the process of damage to buildings. Rust cannot be avoided, but it can control its rate. St.37 carbon steel is the most widely used material for various types of building construction. Therefore, it is necessary to carry out experimental tests regarding the rate of corrosion and its effect on the strength of steel. In this research, using St.37 steel plates, the corrosion process was carried out by leaving the specimens in an open space, immersing the specimens in sea water, and immersing the specimens in fresh water for 15 days. The aim of this research is to analyze the corrosion rate and its effect on the strength of St.37 carbon steel material. Based on the research results, the average corrosion rate of test plates in open spaces was 0 MPy with an extraordinary resistance category; soaked in sea water 14.76 MPy with good category; and soaked in fresh water 39.37 MPy with the fair category. Meanwhile, based on the tensile test results, the average strength was 560.8 MPa for objects, 510.4 MPa, and 492.8 MPa, respectively. This corrosion rate affects the strength of the steel, the greater the corrosion rate, the tensile strength of the steel plate decreases.